Impact of Aliovalent Alkaline-Earth metal solutes on Ceria Grain Boundaries: A density functional theory study. (15th February 2021) - Boland, Tara M.; Rez, Peter; Crozier, Peter A.; Singh, Arunima K.
Graphical abstract: Abstract: Ceria has proven to be an excellent ion-transport and ion-exchange material when used in polycrystalline form and with a high-concentration of aliovalent doped cations. Despite its widespread application, the impact of atomic-scale defects in this material are scarcely studied and poorly understood. In this article, using first-principles simulations, we provide a fundamental understanding of the atomic-structure, thermodynamic and electronic properties of undoped grain-boundaries (GBs) and alkaline-earth metal (AEM) doped GBs in ceria. Using density-functional theory simulations, with a GGA+U functional, we find the Σ 3 (111)/[ 1 ¯ 01] GB is energetically more stable than the Σ 3 (121)/[ 1 ¯ 01] GB due to the larger atomic coherency in the Σ 3 (111)/[ 1 ¯ 01] GB plane. We dope the GBs with ∼ 20% [M] G B (M=Be, Mg, Ca, Sr, and Ba) and find that the GB energies have a parabolic dependence on the size of solutes, the interfacial strain and the packing density of the GB. We see a stabilization of the GBs upon Ca, Sr and Ba doping whereas Be and Mg render them energetically unstable. The electronic density of states reveal that no defect states are present in or above the band gap of the AEM doped ceria, which is highly conducive to maintain low electronic mobility in this ionic conductor. The electronic properties, unlike the energetic properties, exhibit complex inter-dependence on the structure and chemistry of the host and the solutes. This work makes advances in the atomic-scale understanding of aliovalent cation doped ceria GBs serving as an anchor to future studies that can focus on understanding and improving ionic-transport.